HARMONIZATION BETWEEN CUSTOMS AND ISLAM IN THE JALAWASTU COMMUNITY (State Islamic University (UIN) of Sunan Ampel Surabaya, 2022)
There is a growing study concerning various processes of localisation of widely recognised world religions and universalization of local traditions currently, notably associated with the field of religious moderation. One of the issues being stressed is how Islam is able to establish and coexist in harmony with local cultures. This study examines the interaction of Islam with Indonesian indigenous traditions in West Java called Jalawastu, the existence of which continues to present. In other words, this study aims to analyze the religious-cultural lifestyle of the Jalawastu customary community, which have long been practised. A qualitative approach with an ethnographic method was applied. The results of this study illustrate that the relationship between Islam and Jalawastu traditions is in harmony and balance. Those are markedly indicated in the community’s daily life. They are both practising Islamic teachings and performing ancestral traditions. The community’s compliance with their customs brings about the long existence of the traditions even until this modernized era. To sum up, Jalawastu traditions and Islam are the ways through which humanitarian relationships and local wisdom could be reinforced in the era of globalization.